TANTANGAN DEKADENSI MORAL PERSPEKTIF KAJIAN HADITS ARBAIN AL NAWAWIYAH - Ahmad Za'imul Umam; Abdul Muhid (Al-Hayat Al-Istiqomah Foundation, 2020)
The phenomenon of moral decadence is a topic that never dims. Like an endless sea, problem after problems related to the moral decline of the nation's children continues to roll over time. Religious education has an important role in overcoming moral problems that never end. Hadith as the basis of the second Islamic law certainly has a very basic position in Islamic education. Among the thousands of hadiths in the Islamic books, there are 40 hadith selected by Imam Nawawi, then collected in a book called al-arbain al-nawawiyah. The book al-arbain al-nawawiyah received an extraordinary reception from all corners of the world, even the book became a mandatory lesson in Indonesian Islamic Boarding Schools in general. The development of the times brought its challenges in moral matters, especially for the millennial generation. Presumably, the actualization and contextualization of moral values ​​in the book needs to be done. So that found moral values ​​that are relevant to the times. In the end, moral values ​​can easily be understood and practised. And after researching the study of literature from various related references, the authors find that there are moral values ​​that are relevant for overcoming the problem of decadence that is increasingly afflicting. So it is proper for moral studies to be found in the book of al-arbain al-nawawiyah to be studied not only in pesantren but also in other formal and informal institutions.